The Use of Menthol in Skin Wound Healing-Anti-Inflammatory Potential, Antioxidant Defense System Stimulation and Increased Epithelialization - Ariane Leite Rozza; Fernando Pereira Beserra; Ana Júlia Vieira; Eduardo Oliveira de Souza; Carlos Alberto Hussni; Emanuel Ricardo Monteiro Martinez; Rafael Henrique Nóbrega; Cláudia Helena Pellizzon (MDPI AG, 2021)
Wound healing involves inflammatory, proliferative, and remodeling phases, in which various cells and chemical intermediates are involved. This study aimed to investigate the skin wound healing potential of menthol, as well as the mechanisms involved in its effect, after 3, 7, or 14 days of treatment, according to the phases of wound healing. Skin wound was performed in the back of Wistar rats, which were topically treated with vehicle cream; collagenase-based cream (1.2 U/g); or menthol-based cream at 0.25%, 0.5%, or 1.0% over 3, 7, or 14 days. Menthol cream at 0.5% accelerated the healing right from the inflammatory phase (3 days) by decreasing mRNA expression of inflammatory cytokines TNF-α and Il-6. At the proliferative phase (7 days), menthol 0.5% increased the activity of antioxidant enzymes SOD, GR, and GPx, as well as the level of GSH, in addition to decreasing the levels of inflammatory cytokines TNF-α, IL-6, and IL-1β and augmenting mRNA expression for Ki-67, a marker of cellular proliferation. At the remodeling phase (14 days), levels of inflammatory cytokines were decreased, and the level of Il-10 and its mRNA expression were increased in the menthol 0.5% group. Menthol presented skin wound healing activity by modulating the antioxidant system of the cells and the inflammatory response, in addition to stimulating epithelialization.